Providing a Model for Creating Happiness in High Schools - Mohammad Taheri, Maryam; Veissi, Gholamreza; Fazlollahi, Seifollah (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study was conducted with the aim of "providing a model for creating happiness and vitality in high schools".Methodology: The present study was a descriptive (qualitative and quantitative) method in terms of practical purpose, field method and data collection method in terms of practical purpose. The statistical population of this study was 30 experts in the field of happiness, 30,000 high school students, 4800 high school teachers in Alborz, about 80 high school girls and finally high school experts in the general administration. The education department has about 55 members. Based on the principle of saturation in the interview, a sample number of comments from 21 experts was recorded. Based on the Cochran's formula, 380 high school students, 355 high school teachers, 67 high school principals, and 48 school principals were appointed. Data collection method was used in the qualitative part of the field method for semi-structured interview and in a small part of the researcher-made questionnaire. The formal validity and content of the questionnaire were performed by experts, supervisors and advisors, and its reliability was obtained by Cronbach's alpha. The total questionnaire was 0.98, which was distributed and summarized. The influential components were extracted and based on it, the proposed research model consisted of four main sections including the philosophy and objectives of the model, theoretical foundations, conceptual framework and executive steps.Findings: According to the results obtained from the perspective of the participants in the research, 5 factors of physical space (physical), educational activities (cultural-artistic), educational activities, comprehensive characteristics, and the financial situation of the school in the form of 10 components, physical space, component of exciting situations, holding extracurricular workshops, job skills and individual characteristics of school staff, quality of educational content, scientific-research activities, ethical-social, characteristics Emotional-psychological, family, and school financial status have contributed to the creation of happiness and vitality in high schools and educational settings.Conclusion: Student happiness as an important part of teaching if students need education and emotional needs can lead to academic achievement and better student performance.